Vegetable growers perception of pesticide use practices, cost, and health effects in the tropical region of Cameroon - Abang, A.F.; Kouamé, C.; Abang, Mathew M.; Hannah, R.; Fotso, A. (2013)
Pesticide use practices of vegetable farmers were investigated during surveys conducted in major vegetable production zones of the humid tropics of Cameroon. The surveys aimed to elucidate farmers’ crop calendar, pesticide spray schedule and frequency. Farmers’ knowledge was determined on pest targets, quantities and major active ingredients used, and training received in vegetable production. It was found that weekly spray of pesticides was the most common practice; 40% of farmers sprayed insecticide, 28% sprayed fungicides. However, 45 and 59% could not identify the insect pests and diseases respectively they were attempting to control. Farmers applied 0.5-9 liters of pesticide per year, 10-49 kg, and 10 to 49 packets of chemicals depending on farm size. Prices of pesticide range from 5000 to 13000 FCFA per liter of insecticide, 6000 to 8500 FCFA per kg of fungicide and 300 to 12000 F per packet. Ninety percent of farmers used a knapsack sprayer and 20% of farmers noticed that their health was affected by pesticides. About 25% of farmers store chemicals at home. Seventy-five percent receive information about agricultural production from other farmers, and have never received any training on pesticide use practices and health effects. The absence of farmer training further increases the danger of pesticide misuse and cost of vegetable production. Less expensive pest management options that are less hazardous to the environment and human health need to be introduced to farmers, and create awareness regarding hazards of mishandling pesticides if the products are to be used by vegetable farmers in Cameroon.